2014
DOI: 10.1007/s00436-014-4076-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental factors on Argulus japonicus occurrence of Guangdong province, China

Abstract: To assess the effects of abiotic factors on Argulus japonicus occurrence in freshwater ecosystem, we sampled fish, free-swimming parasites, and submerged objects from rivers, fish farms, and ponds (reservoirs and lakes) at 27 locations in Guangdong province, China, from July, 2010, to March, 2013. Friedman's test and Spearman's correlation coefficient (r) were used to investigate relationship between A. japonicus occurrence and abiotic factors in three aquatic systems. Correlation of monthly density, mean dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Among the 48 parasite specimens collected, there was high abundance of three taxa (Branchiura, Copepoda and Isopoda) with diversity of six species (Table 2). Alsarakibi et al (2014) reported that the density of argulids was lower in lotic environments such as rivers, in comparison with lentic environments such as fish farms. Vasconcelos & Tavares-Dias (2016) studied the crustacean parasite fauna in six species of fish in a reservoir in the state of Amapá and reported prevalence of 30.4%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 48 parasite specimens collected, there was high abundance of three taxa (Branchiura, Copepoda and Isopoda) with diversity of six species (Table 2). Alsarakibi et al (2014) reported that the density of argulids was lower in lotic environments such as rivers, in comparison with lentic environments such as fish farms. Vasconcelos & Tavares-Dias (2016) studied the crustacean parasite fauna in six species of fish in a reservoir in the state of Amapá and reported prevalence of 30.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Oliveira et al (2017) reported that in 13 host species of the Jari River (state of Amapá), the prevalence of parasites was 63.8%; they collected 399 parasite specimens. However, the diversity of crustacean parasites and their levels of infestation can be influenced by various factors relating to the biology of parasites and hosts, and by environmental factors, among others (CARVALHO et al, 2003;MAMANI et al, 2004;FONTANA et al, 2012;ALSARAKIBI et al, 2014;MIKHEEV et al, 2015;VASCONCELOS & TAVARES-DIAS, 2016). Fish hosts may be are used by these parasites for transportation (CARVALHO et al, 2003), which could be facilitated by migrating fish species.…”
Section: Introductionmentioning
confidence: 99%
“…In temperate climatic regions, temperature has been considered to be the most important factor influencing the seasonality of parasite infracommunities. Consequently, it can directly or indirectly influence ectoparasites crustacean infestations (Jones, 1974;Guzmán et al, 1988;Kadlec et al, 2003;Pech et al, 2010;Alsarakibi et al, 2014 (Sá-Oliveira et al, 2013. These six fish species presents different life habits, once H. unimaculatus has omnivorous diet, mainly consuming algae, detritus and other aquatic invertebrates, and P. falcata is detritivorous, feeding on detritus and microorganisms associated with the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in water temperature may directly influence the rates of parasite establishment and development, the release of infective stages, and transmission between hosts ( Karvonen et al, 2013 ). pH and DO are also related to the prevalence of aquatic parasites ( Alsarakibi et al, 2014 ). In the present study, the abundance of C. schistorchis showed no correlation with water temperature, pH, or DO.…”
Section: Discussionmentioning
confidence: 99%